2020
DOI: 10.3390/ijms21062200
|View full text |Cite
|
Sign up to set email alerts
|

Myocyte Enhancer Factor 2A (MEF2A) Defines Oxytocin-Induced Morphological Effects and Regulates Mitochondrial Function in Neurons

Abstract: The neuropeptide oxytocin (OT) is a well-described modulator of socio-emotional traits, such as anxiety, stress, social behavior, and pair bonding. However, when dysregulated, it is associated with adverse psychiatric traits, such as various aspects of autism spectrum disorder (ASD). In this study, we identify the transcription factor myocyte enhancer factor 2A (MEF2A) as the common link between OT and cellular changes symptomatic for ASD, encompassing neuronal morphology, connectivity, and mitochondrial funct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 68 publications
1
16
0
Order By: Relevance
“…We detected a similar antiapoptotic response of the same cell line, H32 cells, to various concentrations of OXT and the selective agonist TGOT and confirmed the positive effect of AVP on cell viability [5]. Moreover, OXT and AVP exert similar effects on cellular morphology, i.e., neurite outgrowth or retraction, via their respective receptors [4,5,21].…”
Section: Introductionsupporting
confidence: 74%
See 3 more Smart Citations
“…We detected a similar antiapoptotic response of the same cell line, H32 cells, to various concentrations of OXT and the selective agonist TGOT and confirmed the positive effect of AVP on cell viability [5]. Moreover, OXT and AVP exert similar effects on cellular morphology, i.e., neurite outgrowth or retraction, via their respective receptors [4,5,21].…”
Section: Introductionsupporting
confidence: 74%
“…Morphological alterations in neurons consist of neurite outgrowth or retraction. We [4,5] and others [64,65] previously showed that OXT induces morphological alterations in neurons and glia cells in a conventional 2D cell culture. With this study, we hope to prompt future studies that use 3D spheroid models to validate those 2D-derived findings.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…MEF2A is a very important transcriptional regulatory factor, which is necessary for cell differentiation, cell proliferation, cell survival, morphogenesis and other life processes (16,17). The important role of MEF2A in neural differentiation, maturation and synapsis has been supported by a great deal of evidence (18)(19)(20), but its role in cardiovascular disease is still controversial. In 2003, Wang et al (21) revealed that the 21bp deletion in exon 11 of MEF2A was co-isolated from the patient with premature coronary heart disease in a general pedigree, and MEF2A has become the first identified autosomal dominant genetic variation in the risk of coronary heart disease (named ADCAD1).…”
Section: Introductionmentioning
confidence: 99%